ALGORITMO DE COBERTURA DE VÉRTICES - Javier López Wong (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2023)
Problem to solve P=NP, using the coverage problem of a graph that is NP and convert it to P. In the mathematicaldiscipline of graph theory, a vertex cover, simply a graph cover, is a set of vertices such that each edge of the graph isincident to at least one vertex of the set. The problem of finding the smallest vertex coverage in a graph is called the vertexcoverage problem. In computational complexity theory, it has been shown that this is an NP-complete problem. An NP-complete problem is that it is not known if it has a Polynomial solution. I have found an algorithm that proves that it is Polynomial.